Long-term PM(2.5) Exposure and Neurological Hospital Admissions in the Northeastern United States - Kioumourtzoglou, Marianthi-Anna (Environ Health Perspect, 2015)
BACKGROUND: Long-term exposure to fine particles (particulate matter ≤ 2.5 μm; PM(2.5)) has been consistently linked to heart and lung disease. Recently, there has been increased interest in examining the effects of air pollution on the nervous system, with evidence showing potentially harmful effects on neurodegeneration. OBJECTIVE: Our objective was to assess the potential impact of long-term PM(2.5) exposure on event time, defined as time to first admission for dementia, Alzheimer’s (AD), or Parkinson’s (PD) diseases in an elderly population across the northeastern United States. METHODS: We estimated the effects of PM(2.5) on first hospital admission for dementia, AD, and PD among all Medicare enrollees ≥ 65 years in 50 northeastern U.S. cities (1999–2010). For each outcome, we first ran a Cox proportional hazards model for each city, adjusting for prior cardiopulmonary-related hospitalizations and year, and stratified by follow-up time, age, sex, and race. We then pooled the city-specific estimates by employing a random effects meta-regression. RESULTS: We followed approximately 9.8 million subjects and observed significant associations of long-term PM(2.5) city-wide exposure with all three outcomes. Specifically, we estimated a hazard ratio (HR) of 1.08 (95% CI: 1.05, 1.11) for dementia, an HR of 1.15 (95% CI: 1.11, 1.19) for AD, and an HR of 1.08 (95% CI: 1.04, 1.12) for PD admissions per 1-μg/m(3) increase in annual PM(2.5) concentrations. CONCLUSIONS: To our knowledge, this is the first study to examine the relationship between long-term exposure to PM(2.5) and time to first hospitalization for common neurodegenerative diseases. We found strong evidence of association for all three outcomes. Our findings provide the basis for further studies, as the implications of such exposures could be crucial to public health. CITATION: Kioumourtzoglou MA, Schwartz JD, Weisskopf MG, Melly SJ, Wang Y, Dominici F, Zanobetti A. 2016. Long-term PM(2.5) exposure and neurological hospital admissions in the northeastern United States. Environ Health Perspect 124:23–29; http://dx.doi.org/10.1289/ehp.1408973